DFT models for copper(II) bispidine complexes: Structures, stabilities, isomerism, spin distribution, and spectroscopy - Atanasov, Mihail; Comba, Peter; Martin, Bodo; Müller, Vera; Rajaraman, Gopalan; Rohwer, Heidi; Wunderlich, Steffen (Journal of computational chemistry, 2006)
Various DFT and ab initio methods, including B3LYP, HF, SORCI, and LF‐density functional theory (DFT), are used to compute the structures, relative stabilities, spin density distributions, and spectroscopic properties (electronic and EPR) of the two possible isomers of the copper(II) complexes with derivatives of a rigid tetradentate bispidine ligand with two pyridine and two tertiary amine donors, and a chloride ion. The description of the bonding (covalency of the copper–ligand interactions) and the distribution of the unpaired electron strongly depend on the DFT functional used, specifically on the nonlocal DF correlation and the HF exchange. Various methods may be used to optimize the DFT method. Unfortunately, it appears that there is no general method for the accurate computation of copper(II) complexes, and the choice of method depends on the type of ligands and the structural type of the chromophore. Also, it appears that the choice of method strongly depends on the problem to be solved. LF‐DFT and spectroscopically oriented CI methods (SORCI), provided a large enough reference space is chosen, yield accurate spectroscopic parameters; EDA may lead to a good understanding of relative stabilities; accurate spin density distributions are obtained by modification of the nuclear charge on copper; solvation models are needed for the accurate prediction of isomer distributions. © 2006 Wiley Periodicals, Inc. J Comput Chem 27: 1263–1277, 2006